Nilai-Nilai Kehidupan dalam Naskah Drama Kibar Bendera Si Sarto di Halaman Rumah Karya Rodli TL (Kajian Pragmatik) - Nasution, Melinda (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Drama as a genre of literature, has its own characteristics compared to other genres, namely poetry and fiction. Drama is unique from the point of view of using language and conveying its message and useful values ??for its readers. However, often the delivery of messages and values ??through character conversations is often not caught by the reader because dialogue in drama often uses connotative words that have ambiguity or indirectness of expression. The presentation of language in drama literary works is in the form of using behavioral instructions that describe the atmosphere and using the dialogue of the characters. In terms of message content, the playwright tells human life with its various problems. This study discusses the values ??of life that exist in the drama script